APPLICATION OF OCEANOGRAPHIC DATA ON ILLEGAL FISHING SURVEILLANCE FOR SUPPORTING MARITIME SECURITY (CASE STUDY: NORTH NATUNA SEA) - Raymundus Putra Situmorang; Yosy Gustasya; Muhammad Afrisal; Supriyadi Supriyadi (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2022)
The North Natuna Sea is full of illegal fishing and endangers Indonesia's maritime security. This is because fishery resources/fishery potential in the Natuna Sea is estimated to be worth IDR 5.32 trillion annually. In addition to the potential wealth of fisheries, the strategic location of the Natuna Sea is also the cause of rampant conflicts and illegal fishing activities in this region. Analysis of illegal fishing monitoring in the North Natuna Sea and the use of oceanographic data (sea surface temperature and chlorophyll-a) to monitor illegal fishing in the North Natuna Sea are the two main objectives of this research. The research method used is descriptive qualitative. The results of this study are that surveillance of illegal fishing in the North Natuna Sea has been carried out by the Indonesian Navy, the Indonesian Maritime Security Agency (Bakamla RI), and the Directorate General of Supervision and Control of Marine Resources and Fisheries of the Indonesian Ministry of Maritime Affairs and Fisheries with their duties and functions each. However, this is still not optimal because institutional capacity in supervision is still limited (facilities, human resources, and operational funds). Further findings indicate that oceanographic data has not been used optimally. This is because each agency has a different way of supervision. Automatic Identification Systems and Ship Monitoring Systems are technologies used by each agency in terms of surveillance. Therefore the implementation of illegal fishing surveillance by utilizing oceanographic data can be applied. This can make monitoring more optimal because by using oceanographic data it can be known directly where the potential fishing zones are. For this reason, an open oceanographic database center that can be accessed by various research institutions in Indonesia needs to be established immediately to facilitate the collection or utilization of data by institutions or researchers.